Localized leiomyosarcoma of the uterine cervix with rapid lung metastases - Joao Casanova; Kuan-Gen Huang; Jongrak Thepsuwan; Doris R. Benavides; Chen-Lin Chi (Wolters Kluwer Medknow Publications, 2015)
Cervical sarcomas are extremely rare tumors associated with a poor prognosis. We report the case of a 63-year-old woman who was admitted to our institution due to abnormal vaginal bleeding and abdominal pain. Physical examination revealed a large cervical mass that was biopsied. Pathological features were compatible with a leiomyosarcoma of the uterine cervix. The patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy. All histological and Immunohistochemical findings confirmed the diagnosis of leiomyosarcoma of the cervix. Adjuvant chemotherapy was started but unfortunately the disease progressed and 1 year after completion of the chemotherapy the patient developed lung metastases and eventually died.